Visual search for emotional expressions: Effect of stimulus set on anger and happiness superiority - Savage, R.; Becker, S.; Lipp, Ottmar (Routledge, 2015)
Prior reports of preferential detection of emotional expressions in visual search have yielded inconsistent results, even for face stimuli that avoid obvious expression-related perceptual confounds. The current study investigated inconsistent reports of anger and happiness superiority effects using face stimuli drawn from the same database. Experiment 1 excluded procedural differences as a potential factor, replicating a happiness superiority effect in a procedure that previously yielded an anger superiority effect. Experiments 2a and 2b confirmed that image colour or poser gender did not account for prior inconsistent findings. Experiments 3a and 3b identified stimulus set as the critical variable, revealing happiness or anger superiority effects for two partially overlapping sets of face stimuli. The current results highlight the critical role of stimulus selection for the observation of happiness or anger superiority effects in visual search even for face stimuli that avoid obvious expression related perceptual confounds and are drawn from a single database.